Fungus-assisted reintroduction and long-term survival of two Mexican terrestrial orchids in the natural habitat - Orega-Larrocea, Pilar; Rangel-Villafranco, Mónica (Lankesteriana: International Journal on Orchidology, 2015)
Preservation of genetic diversity of orchids for con- servation and restoration purposes is now a feasible practice after the ecological studies of seed bank dynamics made by several investigators (Batty et al. 2001, Whigham et al. 2006). However, few studies have demonstrated the reliability of reintroduction of several species into their natural habitat and less, managing symbiotic fungus (Ramsay and Dixon 2003, Zettler et al. 2003).